Necessità delle immagini: artisti a fianco dei botanici nel Sei-Settecento (Altre Modernità, 2013)
The art of botanic illustration takes place in two fields: illustrating to botanic texts and still life.From the first half of the XVII Century the plantes introduced in Europe from faraway land, Asia and the New World, encourage a more attentive study than before by the naturalists. The paintings are no more purely ornamental, but they become an integral part of the text. Naturalists try to solicite the collaboration of the best contemporary painters for the illustrational part of their work.The first part of this text is dedicated to the relationship between botanists and artists particularly regarding plants introduced into Europe from America. Of great interest are the result of the Earl of Nassau-Siegen’s expedition (1637-1644), whose following included cartographs, naturalists and painters, the latter's whose task was to document the scenary, the indigenous population, the flora and the fauna.The second part deals with still life, a kind of painting that might seem timeless, at least as to the subjects, but even in this field changes in history may be observed, some of which are illustrated in the text. The iconographic sources, however must always be examined very carefully and together with other sources, because they are often tied to traditional schemes.